THE EFFECT OF APPLYING VENN DIAGRAM STRATEGY ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Emi Agusriani Samosir; Berlin Sibarani (Universitas Negeri Medan, 2012)
This study was aimed at finding out the effect of applying Venn Diagram Strategy on students’ achievement in reading comprehension. This study was conducted with an experimental design. The population of this study was the first year students in the academic year 2012/2013 at SMK Prayatna-1 Medan. There were sixty students taken as the sample of the research. The sample was divided into two groups: the first group (30 students) as the experimental group and the second group (30 students) as the control group. The experimental group was taught by applying the Venn Diagram Strategy, while the control group was taught without the Venn Diagram Strategy. The instrument for collecting data was a multiple choice test which consisted of 40 items. To obtain test reliability, the researcher used the Kuder -Richardson (KR-21) formula. The calculation showed that the reliability of the test was 0.66. The data were calculated by using the t-test formula. The result of the analysis showed that the t-observed (5.02) was higher than t-table (2.00) at the level of significance (α) 0.05 and the degree of freedom (df) 58. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. It means that teaching reading comprehension through the Venn Diagram Strategy significantly affected reading comprehension. Key Words: Venn Diagram Strategy, Reading Comprehension, Student Achievement.